An Overview of the Removal Phosphorus in Wastewater - Norwardatun Binti Abd Roni; Adnan, Suraya Hani; Hamidon, Nuramidah; Tuan Ismail, Tuan Noor Hasanah (Journal of Advanced Industrial Technology and Application, 2020)
The high levels of phosphorus (P) removal occurring through human activities contributes to Eutrophication. Therefore for justifying this problem, it is important to understand the quantity of P flows of the different filter materials. This paper provides an overview on the different filter media used for P removal from wastewater. It describes familiarities from other countries on performance of various different filter media for phosphorus removal. The filter materials consist of natural materials, industrial by-products and man-made products. Most filters have been investigated in batch and column studies in laboratory. The results from these investigations vary but a few filters such slag materials and recycled concrete aggregates have demonstrated promising properties with regard to P removal capacity. A good hydraulic conductivity, the chemical composition of the adsorption media is a critical factor. Because phosphorus is removed via sorption and precipitation processes, Calcium (Ca), Iron (Fe) and Aluminium (Al) content is important in efficient P removal. Thus filter media should be selected very carefully. In such systems, appropriate pre-treatment will also allow for a longer lifetime of the filter media, by decreasing the risk of clogging and allowing one to use finer reactive filter media with higher sorption capacity. Additional important factors determining the applicability of filter materials for removal of P for instance saturation time, availability at a local level, content of heavy metals, and the recyclability of saturated filter media as fertilizer should be taken into consideration. The usage of these alternatives filters materials will ease the environmental problems that are currently perceived globally.